Carotid Artery Stiffness and Cognitive Decline Among Women With or at Risk for HIV Infection. (1st July 2018) - Huck, Daniel M.; Hanna, David B.; Rubin, Leah H.; Maki, Pauline; Valcour, Victor; Springer, Gayle; Xue, Xiaonan; Lazar, Jason; Hodis, Howard N.; Anastos, Kathryn; Kaplan, Robert C.; Kizer, Jorge R.
Abstract : Background: Vascular stiffness is associated with aging and cognitive impairment in older populations without HIV. HIV has been linked to increased vascular stiffness. We examined whether vascular stiffness relates to cognitive decline at younger ages in women with or at risk for HIV. Methods: We evaluated the association of carotid artery stiffness with decline in neuropsychological test performance among participants in the Women's Interagency HIV Study and assessed whether HIV modified the association. Baseline carotid stiffness, defined by the distensibility index, was determined at a single visit using carotid artery ultrasound. Longitudinal neuropsychological testing from 2004–2016 included Trail Making Tests A and B and the Symbol Digit Modalities Test. Relationships were assessed with linear mixed-effect models adjusted for demographic, behavioral, cardiometabolic, and neuropsychological factors. Results: Among 1662 women (1192 [72%] HIV+), median baseline age was 41 years (interquartile range 34–47), with 60% non-Hispanic black and 28% Hispanic. Lower baseline distensibility (greater carotid stiffness) was associated with greater decline in neuropsychological test scores over 10-year follow-up as measured by Symbol Digit Modalities Test (adjusted β = −0.06 per SD, P < 0.001), Trail Making Test A (β = −0.08 per SD; P < 0.001), and Trail Making Test B (β = −0.08 per SD; P < 0.001). Changes in cognitive function did not differ by HIV serostatus, or HIV-related factors. Conclusions: Higher carotid stiffness was independently associated with faster decline in executive functioning, information processing, and psychomotor speed even in mostly middle-aged minority women and regardless of HIV serostatus. Our study highlights the need for cardiovascular risk factor modification to prevent premature cognitive deterioration in this at-risk population. Abstract : Supplemental Digital Content is Available in the Text.